Isolation and Characterization of Multi-Protein Complexes Enriched in the K-Cl Co-transporter 2 From Brain Plasma Membranes - Smalley, Joshua L.; Kontou, Georgina; Choi, Catherine; Ren, Qiu; Albrecht, David; Abiraman, Krithika; Santos, Miguel A. Rodriguez; Bope, Christopher E.; Deeb, Tarek Z.; Davies, Paul A.; Brandon, Nicholas J.; Moss, Stephen J. (Frontiers in Molecular Neuroscience, 2020)
Kcc2 plays a critical role in determining the efficacy of synaptic inhibition, however, the cellular mechanism neurons use to regulate its membrane trafficking, stability and activity are ill-defined. To address these issues, we used affinity purification to isolate stable multi-protein complexes of Kcc2 from the plasma membrane of murine forebrain. We resolved these using Blue-native polyacrylamide gel electrophoresis (BN-PAGE) coupled to LC-MS/MS and label-free quantification. Data are available via ProteomeXchange with identifier PXD021368. Purified Kcc2 migrated as distinct molecular species of 300, 600 and 800 kDa following BN-PAGE. In excess of 90% coverage of the soluble N- and C-termini of Kcc2 was obtained. In total we identified 246 proteins significantly associated with Kcc2. The 300kDa species largely contained Kcc2, which is consistent with a dimeric quaternary structure for this transporter. The 600 and 800 kDa species represented stable multi-protein complexes of Kcc2. We identified a set of novel structural, ion transporting, immune related and signaling protein interactors, that are present at both excitatory and inhibitory synapses, consistent with the proposed localization of Kcc2. These included spectrins, C1qa/b/c and the IP3 receptor. We also identified interactors more directly associated with phosphorylation; Akap5, Akap13 and Lmtk3. Finally, we used LC-MS/MS on the same purified endogenous plasma membrane Kcc2 to detect phosphorylation sites. We detected 11 sites with high confidence, including known and novel sites. Collectively our experiments demonstrate that Kcc2 is associated with components of the neuronal cytoskeleton and signaling molecules that may act to regulate transporter membrane trafficking, stability, and activity.